Integrating Multiple Counselling Approaches for Addressing Extreme Unlovable Feelings in a Muslim Client. - Suwarjo, Suwarjo; Sutanti, Natri; Kurniawan, Luky (Pertanika Journal of Social Sciences & Humanities, 2026)
Integrating spiritual counselling with other counselling approaches is an important factor in achieving a positive outcome for Muslim clients. This study aimed to analyse the process and outcome of counselling for a Muslim client experiencing extreme unlovable feelings, who participated in ten sessions of an integrative counselling focused on the Spiritual Emotional Freedom Technique (SEFT) for 10 sessions. The research employed a qualitative approach, using a systematic case study. The data included counselling notes, interview results with the client and the counsellor, and a standard rating scale. This research identified five important results in the counselling process, 1) personal growth after undergoing counselling; 2) the integrative counselling including Spiritual Emotional Freedom Technique (SEFT) is effective for the client in this context; 3) the counsellor personality had an important role in the changes and the growth; 4) the client and the counsellor were able to demonstrate good ethical boundaries; and 5) there was a transpersonal process of getting closer to the God (Allah). This research recommends the importance of a combination of the modalities used by the counsellor, the counsellor's personality, and ethical boundaries in supporting the discovery of direction and personal development.